Variscan structural evolution of the western High Atlas and the Hauouz plain (Morocco) - Dias, Rui (2012)
The Variscan belt is one of the major geological features of Morocco. Based on the paleogeography of the Paleozoic formations and related tectonometamorphic evolution, different domains have been proposed for this segment of the orogen. The Western High Atlas is one of such domains, which is usually considered as an external zone of the orogeny where most of its deformation is ascribed to a first and main Variscan tectonic event (D1). Such a deformation has been detailed described in previous studies that emphasize an N-S folding with a western facing. These folds, having an axial plane cleavage, locally rotate in a continuous way to a NE-SW trend, becoming subparallel to major dextral coeval shear zones. In this work a late D1 stage is characterized (D1b) which is restricted to the vicinity of regionally scale sinistral WNW-ESE shear zones. The previous structures (D1a) are deflected by these shears with a kinematics compatible with their sinistral movement. The previously described Lalla Takerkoust fault in the Haouz plain and the newly proposed Adassil shear zone are ascribed to such event. The ENE-WSW dextral shears and the WNW-ESE sinistral ones should be considered as conjugated systems during the D1 event. Nevertheless, as the dextral family is synthetic of the oblique collision between Laurentia and Gondwana, not only their movement slightly predates the onset of the sinistral shears, but they also present a much more pervasive distribution.